(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Due to increasing pressure to adopt sustainable practices in the business the incorporation of Green Innovation as part of strategic direction is paramount for organizations. The mediating role of Entrepreneurial Orientation (EO) in relation between Green Innovation and sustainable corporate performance (SCP) is guaranteed by its proactive, risk-taking, innovative character. It is evident that the firms with a high level of Entrepreneurial Orientation are more prepared to deal with the issues of adopting green technologies, operations, and goods, which would improve their sustainability performances. Green Innovation (GI) that deals with green solutions for organizations goes further than satisfying legal measures as it also opens the gate towards competition in the market. Fresh from this article, the extent at which EO impacts GI integrated with SCP in the dairy industry is discussed. This analysis of the green marketing mix and consumers’ purchase intentions offers insights for further research that tested the impact of organizational factors, including Entrepreneurial Orientation, so companies can advance both a sustainable environment and corporation’s profitability.